Antifungal and anti-biofilm activities of patchouli alcohol against Candida albicans - Qiulei Zhang; Jingxiao Zhang; Yu Zhang; Yujie Sui; Yang Du; Longfei Yang; Yongjie Yin (Elsevier, 2024)
The opportunistic fungal pathogen Candida albicans could cause severe clinical outcomes which could be exacerbated by the scarcity of antifungals. The capacity of C. albicans to form biofilms on medical devices that are hard to eradicate, further deepen the need to develop antifungal agents. In this study, we, for the first time, showed that patchouli alcohol (PA) can inhibit the growth of multiple C. albicans strains, as well as four other Candida species, with MICs of 64 μg/mL and MFCs from 64 to 128 μg/mL. The biofilm formation and development, adhesion, yeast-to-hyphal transition and extracellular polysaccharide of C. albicans can be inhibited by PA in a concentration-dependent manner. Confocal microscopy analyses of cells treated with PA showed that PA can increase the membrane permeability and intracellular reactive oxygen species (ROS) production. In C. elegans, PA did not influence the survival below 64 μg/mL. In this study PA demonstrated antifungal and antibiofilm activity against C. albicans and our results showed the potential of developing PA to fight Candida infections.